We the Dutertards, You the Dilawan. IN Commentary [column] - Tiojanco, Bryan Dennis Gabito (2017)
They way many Filipinos today think about politics undermines the basic belief that makes democracies stable: that citizenry is united by a set of first principles and institutions. Thus, the words"We the People" launches almost every democratic constitution in the world today.
Keywords: Duterte administration -- Criticism